Association between methylenetetrahydrofolate reductase C677T polymorphism and cerebral small vessel disease: a systematic review and meta-analysis - Zheng, Hao-tao; Lai, Wen-wen; Wang, Jian-jun; Kong, Fan-xin; Cai, Hao-bin; Lin, Song-jun; Wang, Xu; Cai, Dong-bin; Pi, Min; Qin, Xiu-de (Frontiers in Neurology, 2025)
ObjectiveThis systematic review and meta-analysis aimed to evaluate the association between the methylenetetrahydrofolate reductase (5,10-methylenetetrahydrofolate reductase, MTHFR) cytosine (C)677thymine (T) polymorphism and cerebral small vessel disease (CSVD), addressing potential sources of heterogeneity and publication bias.MethodsAn extensive search of databases, including PubMed, the Excerpta Medical Database, and The Cochrane Database of Systematic Reviews, was conducted to identify studies assessing the prevalence of the MTHFR C677T variant associated with CSVD subtypes in humans. Random or fixed effects models were used to accommodate heterogeneity across the study results. Odds ratios (ORs) and weighted mean differences with 95% confidence intervals (CIs) were used for pooled analyses of the relationships between the MTHFR C677T variant associated and CSVD subtypes. Subgroup analyses and assessments of publication bias were performed using Stata software.ResultsNineteen studies involving 12,441 participants were included. Significant associations were observed across all genetic models: recessive (OR = 1.33; 95%CI = 1.16, 1.52), dominant (OR = 1.25; 95%CI = 1.14, 1.37), allelic (OR = 1.24; 95%CI = 1.14, 1.35), TT vs. CC (OR = 1.42; 95%CI = 1.25, 1.61), and CT vs. CC (OR = 1.20; 95%CI = 1.09, 1.32). Subgroup analyses revealed stronger associations in CSVD-NOS. However, the trim-and-fill method indicated significant publication bias, with adjusted ORs becoming non-significant (recessive model: OR =1.10, 95% CI=0.81, 1.49). Heterogeneity was low to moderate across models (I2 = 14.2–32.4%).ConclusionThis study highlights the significant association between MTHFR C677T genotyping and CSVD. Early assessment of MTHFR C677T genotyping during the clinical evaluation of elderly patients may improve patient management and reduce the adverse prognostic impact of the CSVD burden. However, further validation of these findings in large-scale, high-quality prospective studies is required.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/; identifier: CRD42023339320.